Suppression of yeast RNA polymerase III mutations by FHL1, a gene coding for a fork head protein involved in rRNA processing. - Hermann-Le Denmat, S (1994)
The FHL1 gene was isolated by screening for high-copy-number suppressors of conditional RNA polymerase III mutations. This gene is unique on the yeast genome and was located close to RPC40 and PRE2 on the right arm of chromosome XVI. It codes for a 936-amino-acid protein containing a domain similar to the fork head DNA-binding domain, initially found in the developmental fork head protein of Drosophila melanogaster and in the HNF-3 family of hepatocyte mammalian transcription factors. Null mutations caused a severe reduction in growth rate and a lower rRNA content that resulted from defective rRNA processing. There was no detectable effect on mRNA splicing. Thus, the Fhl1p protein plays a key role in the control of rRNA processing, presumably by acting as a transcriptional regulator of genes specifically involved in that process. Moreover, mutants carrying the RNA polymerase III mutations were slightly defective in rRNA processing. This accounts for the isolation of FHL1 as a dosage-dependent suppressor and suggests that rRNA processing depends on a still-unidentified RNA polymerase III transcript.